An undetectable polymerase chain reaction signal in routine HIV plasma viral load monitoring is associated with better virological outcomes in patients receiving highly active antiretroviral therapy1. Issue 8 (8th May 2013) - Pugliese, P; Delpierre, C; Cuzin, L; Poizot‐Martin, I; Rey, D; Saune, K; Cottalorda, J; Bettinger, D; Delaugerre, C; Hoen, B; ,
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to assess whether patients with undetectable viraemia [a negative polymerase chain reaction result (PCRneg)] and those with plasma viral load (PVL) < 40 HIV‐1 RNA copies/mL but a detectable (positive) PCR signal (PCRpos) had different outcomes in terms of the development of blips and virological failure (VF). Methods A multicentre observational database analysis was carried out. Data for patients whose highly active antiretroviral therapy (HAART) regime had been unchanged for ≥ 6 months by 1 January 2008, whose first two PVL measurements of 2008 were < 40 copies/mL and who had at least five PVL measurements between 1 January 2008 and 31 December 2010 were extracted from a multicentre observational database of 4928 patients receiving HAART. PVL assays used during this period had a detection threshold of 20 or 40 copies/mL. Undetectable PVL at baseline (BLPCRneg) was defined as PCRneg at the first two PVL determinations of 2008. Multivariable Cox regression analysis was performed to investigate factors associated with the occurrence of blips and VF, defined as two consecutive PVL measurements > 40 copies/mL. Results Of the 1957 patients included in the study (mean age 47 years; median antiretroviral exposure 10.3 years), 1312 had BLPCRneg. Outcome events included 322 blips and 139 VFs, with incidence rates being significantly lower in patients with BLPCRneg than in those with BLPCRpos [13.0% vs. 23.4% (P < 0.0001) and 5.1% vs. 11.2% (P < 0.0001), respectively]. In multivariable analysis, BLPCRneg was associated with a reduced risk of blips [hazard ratio (HR) 0.58; 95% confidence interval (CI) 0.47–0.73; P < 0.0001] and VF (HR 0.44; 95% CI 0.31–0.62; P < 0.0001). Conclusions Patients with PCRneg had better virological outcomes than those with PVL < 40 copies/mL but detectable viraemia. This suggests that the 'no‐signal' information provided by currently commercially available HIV RNA quantification assays should be used routinely.